Why Creative Intelligence is Hard to Find - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "Why Creative Intelligence is Hard to Find." Behavioral and Brain Sciences 11, no. 2 (1988): 253.